Experimental thermal survey of automotive turbocharger. (June 2020) - Alaviyoun, Seyed Shahabeddin; Ziabasharhagh, Masoud
Turbochargers are commonly used in the automotive industry due to their ability to increase the specific power output of internal combustion engines. Heat transfer from the turbine to the compressor can strongly influence the turbocharger performance. Therefore, it is essential to consider heat transfer properties of the turbochargers. Existing heat transfer models are generally limited to the specific situations on the turbocharger test rig or the engine test bench, which are different to the real conditions of engine operation in a vehicle. Accurate modeling and calculation of the heat transfer require a more precise measurement study. In this research, we evaluate the temperature distribution of the turbocharger walls using an engine test bench and also a vehicle that are both equipped with the same instrumented turbocharger. Thermocouple measurements and thermography pictures were used to determine the temperature distributions of the turbocharger. Different heat transfer phenomena of turbocharger have been measured and analyzed. In addition, the effect of heat transfer on compressor efficiency is investigated. Several tests have been conducted, including a vehicle on a flat surface and also during an uphill climb with a trailer load hitched. The results of vehicle warm-up test show that the compressor housing has a higher temperature gradient in comparison with the engine test bench. The velocity of the air around the turbocharger is a factor that contributed toward the differences between an engine test bench and typical vehicle conditions.